Sher Shah Suri - Matta, Basheer Ahmad Khan (Oxford University Press, 2005)
This is an account of Sher Shah Suri--a man of surpassing personal excellence, a great and exemplary ruler, and the greatest leader ever produced by the Afghans. The book seeks to examine and evaluate his performance in all these capacities: to explore the pith and essence of the man and determine his place in the currents of Indian history, as well as in the independent stream of Afghan history. At his death in 1545, Sher Shah left behind an empire stretching from the Indus to the Bay of Bengal. However, Sher Shah's place in history rests not on his military exploits alone, but on the exemplary efficiency of his rule, the many far-reaching improvements that he effected in all spheres of government, and the splendid measures that he instituted for the good of the general public. This is a history of Sher Shah and the interrelatioship between India and the Afghans, and the great currents and countercurrents of events pertaining in the age. Moreover, and most significantly, its conclusions are drawn from the cardinal lessons ingrained in Indian history